การใช้ภาษาอังกฤษในพุทธสถาน - อภัยโส, พลภัทร (วารสารศรีล้านช้างปริทรรศน์, 2018)
ประเทศไทยเป็นเมืองแห่งพระพุทธศาสนา เนื่องจากบรรพชนชาวไทยได้พากันเชื่อถือและยึดเอาคำสอนของพระพุทธศาสนามาเป็นแนวทางในการดำเนินชีวิตมาเป็นเวลานานนับพันปีนับตั้งแต่ยุคสุโขทัยกระทั่งถึงปัจจุบัน ดังนั้นแทบจะทุกพื้นที่ในประเทศไทยจึงเต็มไปด้วยวัดวาอาราม โบราณสถานและโบราณวัตถุที่เกี่ยวข้องกับพระพุทธศาสนามากมาย นักท่องเที่ยวต่างชาติที่มาเยี่ยมชมประเทศไทยล้วนต้องได้สัมผัสกับแหล่งท่องเที่ยวที่เกี่ยวข้องกับพระพุทธศาสนาไม่มากก็น้อย ดังนั้นการต้อนรับขับสู้นักท่องเที่ยวต่างชาติในฐานะเจ้าบ้าน คนไทยทุกคนจึงจำเป็นต้องรู้เกี่ยวกับพระพุทธศาสนา โดยเฉพาะคำศัพท์ที่จำเป็น เพื่อจะได้ใช้ติดต่อสื่อสารกับชาวต่างชาติที่ต้องการรู้เรื่องเกี่ยวกับพระพุทธศาสนา           Thailand was regarded as the country of Buddhism since Thai ancestors in the past believed and held Buddhist teachings as their way of life longer than 1,000 years from the reign of Sukhothai Kingdom until now. So, every inch in Thailand was full of several temples, ancient places and things involved with Buddhism. Foreign tourists, more or less, were believed to experience some Buddhist tourism resources. With a warm welcome as good hosts, all Thai people had to know Buddhism and other related things, especially important vocabularies on Buddhism. They were useful for Thai people to communicate with foreigners,  who needed to know Buddhim, in English.